How parents build a case for autism spectrum disorder during initial assessments: 'We're fighting a losing battle'. (February 2017) - O'Reilly, Michelle; Nina Lester, Jessica; Muskett, Tom; Karim, Khalid
Integral to the diagnosis of autism spectrum disorder is the initial assessment through which the existence of a 'problem' is first ascertained. Despite this, there remains limited research on this early part of the diagnostic pathway. In this article, we utilised conversation analysis to examine relevant issues in relation to the practitioner–family interactions that take place within this initial assessment context. Our findings illustrated that parents typically first raised the possibility of the presence of an autism spectrum disorder diagnosis through 'building a case', which professionals were then able to ratify or negate. Furthermore, we found that the assessments unfolded sequentially and clinical decisions were typically reached through a distinctive pattern of interaction. These findings have important implications for clinical practice, including for the study of autism spectrum disorder assessments and diagnosis.